A comparative in vitro and in vivo analysis of the biological properties of the 45S5-, 1393-, and 0106-B1-bioactive glass compositions using human bone marrow-derived stromal cells and a rodent critical size femoral defect model - Kunisch, Elke; Fiehn, Linn Anna; Saur, Merve; Arango-Ospina, Marcela; Merle, Christian; Hagmann, Sébastien; Stiller, Adrian; Hupa, Leena; Renkawitz, Tobias; Boccaccini, Aldo R.; Westhauser, Fabian (Biomaterials advances, 2023)
Since the introduction of the 45S5-bioactive glass (BG), numerous new BG compositions have been developed. Compared to the 45S5-BG, 1393-BG shows favorable processing properties due to its low crystallization tendency and the 1393-BG-based borosilicate 0106-B1-BG exhibits improved angiogenic properties due to its boron content. Despite their close (chemical) relationship, the biological properties of the mentioned BG composition have not yet been comparatively examined. In this study, the effects of the BGs on proliferation, viability, osteogenic differentiation, and angiogenic factor production of human bone marrow-derived mesenchymal stromal cells were assessed. Scaffolds made of the BGs were introduced in a critical-sized femur defect model in rats in order to analyze their impact on bone defect regeneration. In vitro, 1393-BG and 0106-B1-BG outperformed 45S5-BG with regard to cell proliferation and viability. 1393-BG enhanced osteogenic differentiation; 0106-B1-BG promoted angiogenic factor production. In vivo, 0106-B1-BG and 45S5-BG outperformed 1393-BG in terms of angiogenic and osteoclastic response resulting in improved bone regeneration. In conclusion, the biological properties of BGs can be significantly modified by tuning their composition. Demonstrating favorable processing properties and an equally strong in vivo bone regeneration potential as 45S5-BG, 0106-B1-BG qualifies as a basis to incorporate other bioactive ions to improve its biological properties.
Gesehen am 06.12.2023